Schooling, the Puritan imperative, and the molding of an American national identity : education's "errand into the wilderness" - McKnight, Douglas (Studies in curriculum theory., 2003)
Present-day America is perceived by many as immersed in a moral crisis. This text explores the relationship between the purposes of education and the notion of an American identity and morality rooted in the Puritan concept of an "errand into the wilderness."